Construction of Escherichia coli Whole-Cell Biosensors for Statin Efficacy and Production Test - Li, Huanjie; Wang, Qingda; Zhao, Rui; Wang, Yunshan; Xun, Luying; Liu, Huaiwei (Frontiers in Cell and Developmental Biology, 2020)
Statins are widely used cholesterol-lowering drugs. Their potential application in anti-cancer treatment is also under investigation. The individual variance in statin response has been observed, which may be caused by the variation in human HMG-CoA reductase (hHMGR)—the inhibition target of statin drugs. Herein, we reported the design and construction of two E. coli whole-cell biosensors. The first one is statin-efficacy testing sensor, which is composed of two separate modules: a hybrid mevalonate (MVA) pathway and a HMG-CoA sensing system. A truncated hHMGR was used as the key enzyme of the MVA pathway and a promiscuous transcription factor BsFapR was used as the HMG-CoA sensor. When hHMGR was inhibited by statins, HMG-CoA accumulated intracellularly and was sensed by BsFapR, which subsequently turned on its cognate promoter. This biosensor has the potential to be used as a “precision medicine” tool—selecting potent statin drugs for individual patients. The second one is a statin-production testing sensor, which is based on another promiscuous transcription factor AraCM that can sense statins. This biosensor can be used in optimization of statin-producing strains. The prototypes of these two biosensors were successfully constructed and their further optimization is highly expected.